Characterisation of a controllable loop thermosyphon for precise temperature management. (25th February 2021) - Chen, Chuxiong; Cao, Jingyu; Yu, Jingjing; Liu, Weixin; Hu, Mingke; Wang, Qiliang; Jiao, Dongsheng; Ren, Wei; Pei, Gang
Highlights: A controllable loop thermosyphon is designed for precise temperature management. Thermal characteristics in continuous and start-stop operations are examined with various refrigerants. Space temperature can be cooled from 25 °C to 5 °C in 90 min using 23.5% of R407C. Temperature fluctuation is minimised to ± 0.3 °C even the heat source temperature varies. Abstract: Controllable loop thermosyphon in frequently start-stop operation offers an efficient heat transfer regulation. This low-cost device has a great protentional in precise temperature management of refrigerators, industrial buildings, and cutting-edge equipment. In this study, a test platform is built to investigate the thermodynamic characteristics of controllable loop thermosyphon and its effectiveness on precise temperature control of a fresh-keeping box. The comprehensive behaviours in continuous and start-stop operations are explored using R407C, R410A, R404A and R134a as working fluids. The filling ratios for above refrigerants are optimised, and the influence of thermal boundaries are studied. Given a suitable filling ratio of R407C, the average fresh-keeping temperature is reduced from 25 °C to 5 °C in 90 min and to 0 °C in 180 min during continuous operation. In start-stop operation, a minimum fresh-keeping temperature fluctuation of ± 0.3 °C is achieved at various fresh-keeping temperatures. The maximum and average heat transfer rates in the running period are 74.0–94.5 W and 48.3–80.2 W, respectively. Results indicate that the controllable loop thermosyphon with R407C provides efficient heat transfer and thermal control, and thus perform well in precise temperature management.